Lipoid proteinosis and epilepsy: Molecular analysis - Tecellioglu, Mehmet; Kamisli, Ozden; Acar, Ceren; Merge, Hatice; Sozen, Mert; Karaduman, Tugce; Sarac, Gulbahar; Fatih Erbay, Mehmet (Annals of Medical Research, 2021)
None
Keywords: Lipoid Proteinosis; Ecm1; Genetics; Epilepsy.